PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI RESTORAN SAUNG REMPAH SERPONG TANGERANG SELATAN - Evi Savitri; Eko Sudarso (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The purpose of this study was to determine the influence of leadership style and work environment on employee performance at Saung Rempah Restaurant, Serpong, South Tangerang. The research method used was quantitative. The sampling technique used saturated sampling and obtained a sample of 32 respondents. Data analysis used validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, simple linear regression test, and multiple linear regression test, correlation coefficient analysis, determination coefficient test, partial hypothesis test (t test), and simultaneous hypothesis test (f test). The results of this study are a positive and significant influence of leadership style (X1) on employee performance with a Pearson Correlation value of 0.796 which is classified as a strong category. And the work environment (X2) has a significant influence on employee performance with a Pearson Correlation value of 0.878 which is classified as a very strong category. And the results of the multiple correlation coefficient of leadership style (X1) and work environment (X2) on employee performance (Y) by showing an R square value of 0.849, has a very strong relationship level of 0.849. The influence of leadership style (X1) on employee performance has a significant effect on employee performance of 74.6% while the remaining 25.4% is influenced by other factors, the influence of work environment (X2) on employee performance is 60.5% while the remaining 30.5% is influenced by other factors, the influence of leadership style (X1) and work environment (X2) on employee performance (Y) is 72% while the remaining 28% is influenced by other factors. With the hypothesis test, the calculated t value is obtained > t table value or (2.576)> t table 2.04523). The work environment has a significant effect on employee performance and the hypothesis test obtained the calculated t value> t table value or (3.718) < t table 2.04523). Leadership style (X1) and work environment (X2). Hypothesis testing obtained a calculated F value > F table or (37.338 > 3.33).